Cognitive Training in the Domain of Mathematics for Potentially Gifted Children in Primary School - Mirjam G. J. de Vreeze-Westgeest; Bart Vogelaar (MDPI AG, 2022)
This study examined auditive and visual working memory and metacognitive knowledge in 92 gifted children (aged between eight and twelve), utilising a pre-test-training-post-test design, known as the cognitive training design. This approach was used to examine the working memory and metacognitive knowledge of gifted children concerning the progression after a cognitive training programme in arithmetical problem solving, taking into account the role of intelligence. Children were allocated to one of two experimental conditions: children received training after the pre-test (cognitive training condition) or were provided with training after the post-test (control condition). The results show that all children made significant improvements in working memory and metacognition. Intelligence significantly predicted verbal and visual working memory. However, we did not find a meaningful relationship between intelligence and metacognitive knowledge. The cognitive training in arithmetical problem solving seems to bring additional measurable changes in metacognitive knowledge, but not in working memory.